Appropriating Technological Pedagogical Content Knowledge of Basic Education Teacher Using Online Learning Instruction - Manacap, Charismarie; Tagaro, Paul Mari; Cose, Anabelle; Tagaro, Nelia; Larida, Lynn; Chiu, Ditto; Acha, Pedro; Ocba Jr., Pedrito S. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The digitalization of the world community and the advent of Covid-19 pandemic have created impact to the lives of the teachers and other stakeholders. This study provide knowledge on the teachers in terms of, pedagogical, content and technological knowledge in using technology as means of instruction and learning of the students. Findings have showed that teachers were knowledgeable in terms of technology as means of their pedagogical application, content matters and best practices in technology integration. Data further implied that teachers were knowledgeable with tech-ed either online or in the classroom settings. However, data suggests that there were some technical issues were perceived in technology integration.